FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PEGAWAI DINAS BINA MARGA PROVINSI SULAWESI SELATAN - Herianto, Dedy; Mirsa, Sitti (Jurnal Politik Profetik, 2018)
The problem observed in this research is the low level of awareness and responsibility of civil servants at the Office of Highways on road construction, particularly in constructing provincial roads. This research is intended to explore and analyze influencing factors on work motivation of staff at the Office of Highways of South Sulawesi Province. This research applies quantitative descriptive method which covers 224 populations. Using probability sampling random of Slovin, this research picks 69 samples. In analyzing the data, this research applies motivation theory of Herzberg’s intrinsic and extrinsic factors. Intrinsic factor may include performance achievement, recognition, responsibility, progress/change and work development, while extrinsic factor covers salary, work safety, work condition, status, company procedures, and the quality of staff relations. The result shows that the staff work motivation which was assessed using intrinsic factors provides quite good category due to good performance, recognizable performance by others, and organizational progress or change oriented works. Staff motivations which were assessed by applying extrinsic factors, however, show different results. These unsatisfying results happened due to low level of salary, bad status and awkward staff relations.